From goals to action implementing the sustainable development goals. (Asian Development Bank, 2017)
It has been more than a year since the SDGs were adopted, and institutions including ADB are grappling with the demands of delivering on this ambitious new agenda. The 2030 agenda is particularly relevant in the Asia and Pacific region, where impressive progress has been made in reducing extreme poverty, but 330 million people in ADB developing member countries still live on less than 1.90 a day.